Between and within person associations between negative life events and alcohol outcomes in adolescents with ADHD - King, Kevin M. (Psychol Addict Behav, 2017)
Escalations in alcohol use during adolescence may be linked with exposure to negative life events, but most of this research has focused on between person associations. Moreover, adolescents with ADHD may be an especially vulnerable population, reporting more life events, alcohol involvement, and may even be more sensitive to the effects of life events on alcohol outcomes compared to those without ADHD. We tested the between and within person effects of the number and perceptions of negative life events on the development of alcohol use outcomes from age 14 to 17 in 259 adolescents with and without ADHD using generalized estimating equations. Between person differences in exposure to negative life events across adolescence, but not the perception of those events, were associated with a higher likelihood of alcohol use and drunkenness at age 17. Within person differences in life events was associated with alcohol use above and beyond that predicted by an adolescents’ typical trajectory over time. Parent and teacher-reported ADHD symptoms were associated with more negative perceptions of life events, and with greater alcohol use and drunkenness at age 17, but symptoms did not moderate the life event-alcohol association. Interventions should consider the variables that produce vulnerability to life events as well as the immediate impact of life events. That the accumulation of life events, rather than their perceived negativity, was associated with alcohol outcomes, indicates that interventions targeting the reduction of negative events, rather than emotional response, may be more protective against alcohol use in adolescence.